The fruits of ones labor: effort-reward imbalance but not job strain is related to heart rate variability across the day in 35-44-year-old workers - Loerbroks, Adrian; Schilling, Oliver; Haxsen, Volker; Jarczok, Marc N.; Thayer, Julian F.; Fischer, Joachim E. (Journal of psychosomatic research, 2010)
Previous research has suggested that the association between work stress and heart disease is more pronounced in young than in old employees. Similar age specificity may apply to the relation between work stress and heart rate variability (HRV), but data on this issue is sparse. We aimed to assess the age-specificity of the work stress-HRV association in greater detail.
Gesehen am 29.03.2023